Pengembangan Media Pembelajaran Lagu “Senada” Berbasis Artyculate Storyline untuk Meningkatkan Hasil Belajar IPS Kelas IV SD - Dzikruliliam Dzikruliliam; Putri Yanuarita Sutikno (Lembaga Pengembangan Kinerja Dosen, 2026)
Social Studies instruction at the elementary school level plays a strategic role in instilling civic values in students, thereby preparing them to behave as good citizens within the social environment. This study employed a Research and Development (R&D) method conducted in Grade IV at SDN Kebumen 02 using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The findings indicate that the Senada song–based learning media developed using Articulate Storyline 3, which contains material on the diversity of ethnic groups and nations in Indonesia, was designed in accordance with instructional needs, received a “very feasible” rating from both content and media experts, and was proven effective as a supporting medium for Social Studies learning in improving the learning outcomes of Grade IV students, as evidenced by the results of paired t-tests and N-Gain analyses conducted in both small and large groups. This media has also proven effective in improving student learning outcomes, as tested using paired t-tests and N-Gain tests in small and large groups. These results indicate that song-based media can improve student motivation and learning outcomes in social studies.